A systems view on Circular Economy transitions: examining the deceleration of resource flows - Costa, Daniel Guzzo da (2020)
An envisioned Circular Economy (CE) can only be achieved by the transition of consumption and production systems to enhanced modes of resource use. The deceleration of resource flows and appreciation of feedback relationships among the economic and Earth systems are essential to such transitions. Systems thinking is, thus, at the core of CE transitions. However, increasing complexity emerges in CE systems and available tools insufficiently address the experimenting needs of decision-makers in bottom-up and top-down CE transitions. This thesis aims at resolving the following general research question \"How can a systems approach help decision-makers to understand and facilitate CE transitions?\". In this regard, two complementary goals were defined: a theoretical goal of interpreting CE transitions through a systems perspective, and a practical goal of generating tools to facilitate decision-making in CE transitions. The fulfilment of six work packages permits responding to the general research question and complementary goals. Key concepts from the CE, industrial ecology, sustainability transitions, and System Dynamics fields sustain the foundations of the thesis. Modelling and simulation using System Dynamics (SD) bind the descriptive and prescriptive efforts in this thesis through three modelling and simulation studies to examine cases of different scopes: the adoption of a sharing platform by one company, the implementation of nationwide CE strategies implementation for a type of electrical and electronic equipment (EEE) in the Netherlands, and the implementation of collection interventions for post-use smartphones to meet the targets of the Brazilian industrial agreement for EEE (BIAEEE). Each study results in an article that composes the thesis. The three studies enable the proposition of a conceptual model for CE systems, of an open-access tool to examine CE systems (the Circular EEE SD model), of guidelines for examining CE transitions using SD, and discussion of potential insights for business practitioners and policy-makers when applying a systems approach in examining systems with different scopes. The results allow for crucial decisions, and discussions to enabling the urgent deceleration of resource flows in consumption and production systems. This thesis contributes to theory and practice by clarifying the meaning and role of a systems approach to enable CE transitions.